Towards a critical positioning in Social Work - Cerros Rodríguez, Elisa (Interacción y Perspectiva, 2024)
Academic meetups regarding Social Work are doubtlessly an excellent space for reflection on the discipline, which offer up the chance to examine the processes of professional intervention, the role of Social Work, the complexity of the intervened contexts, the ethical and professional implications present in professional interventions, as well as the various theoretical and methodological lenses through which Social Work sees and intervenes. In this sense, the reflections in the present article were exposed in the Iberoamerican Meetup of Social Work Schools, organized by the Social Work School of Zulia through a simposium called Social Work in postmodern times, an academic space which allowed colleagues from different latitudes to share the findings of ongoing investigations, as well as reflections regarding the challenges of Social Work in postmodern times. In this event, the authors of this article presented an analysis stemming from the mexican context, on the relevance of pushing a critical positioning from academic formation, to be projected in professional practice and in organizational capacity, as a guild. This article postulates that the strengthening and recognition of the discipline come alongside a political project that outlines the path of the discipline in Mexico, which doubtlessly ought to have a clear critical and ethical positioning, besides the necessary academic articulation, professional collective, where the present and future of the profession are debated, questioned, and constructed.